Oral candidal carriage in children with and without dental caries - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2007)
Objectives: An epidemiologic study of 213 healthy children was carried out in 2 age groups (4 to 6 and 7 to 12 years) to determine the potential relationships between oral Candida and dental status. Method and Materials: For each child included, a dental examination and mycologic investigation were conducted. The dental examination determined the index values for decayed and filled primary teeth (df-t) and decayed, missing, and filled permanent teeth (DMF-T). Results: In the 4- to 6-year age group, the frequency of oral Candida in children with moderate and high df-t indexes was statistically higher than in caries-free children. By comparison, in the 7- to 12-year age group, high frequency of Candida was observed only in children with high dental indexes (both df-t and DMF-T), but it was not significant. Generally, the intensity of candidal carriage in Candida-positive children was low, and it was not varied as a function of dental caries. Candida albicans was more frequently isolated, and it was the only species present in caries-free children. Other identified species were observed in children with different values of dental indexes. Conclusions: Mycologic examination may constitute a contributory role for epidemiologic studies of dental caries, especially in children under 7 years of age.
Keywords: age; Candida albicans; candidal; carriage; children; dental caries; PREVALENCE; FREQUENCY; YEASTS; FLORA